An isolable iron(ii) bis(supersilyl) complex as an effective catalyst for reduction reactions. Issue 9 (11th February 2019) - Arata, Shogo; Sunada, Yusuke
Abstract : An isolable 14-electron iron bis(supersilyl) complex, Fe[Si(SiMe3 )3 ]2 (THF)2, was successfully synthesized, and catalytic performance toward reduction reactions was also demonstrated. Abstract : An isolable 14-electron iron bis(supersilyl) complex, Fe[Si(SiMe3 )3 ]2 (THF)2, was successfully synthesized from the reaction of FeBr2 with K[Si(SiMe3 )3 ] and its structure was unambiguously determined by single-crystal X-ray diffraction analysis. The complex is coordinatively unsaturated and exhibits high catalytic activity toward the hydrosilylation of carbonyl compounds and the reductive silylation of dinitrogen.